(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Social Media Marketing is the process of promoting products or servicesthrough social media. We are consigned to stressing over the "terrible" social media remarks, fascinating for activities, warm elective business status and understanding situations.The essential portion revolves around security issues with online trades, followed by a discussion of legitimate purchase issues are accompanying section studies the investigation on sexual direction based purchasing measures, followed by an evaluation of sex related purchase intentions and practices, ways to deal with address online security are to be suggested. Models incorporate informal communication and video-sharing destinations like Facebook and YouTube. The term is presently firmly connected with Tim O’Reilly in light of the O’Reilly Media Web 2.0 gathering in 2004. Thus, Web 2.0 unites nearby and globally in a data partnership, despite the fact that the concept suggests another version of the World Wide Web. It does not allude to an update to any specialized information, but rather to aggregate improvements in the ways programming engineers and end-clients use the web.This study aims to determine what percentage of purchases made via social media marketing, and I gathered data from web users using the research technique. According to the data gathered, gents tend to purchase via social media rather than ladies. The choice is determined by the inclination of customer’s commitment and financing factors likewise assume a significant part in social media.